Personalized medicine approach in dental management, abilities and challenges: A review article - Seyed Hamid Jamaldini (Tehran University of Medical Sciences, 2020)
Background and Aims: Advances of genetic science in genomic techniques have led introducing new diagnostic systems to study the diseases or treatment efficacies. In this science, which named "Personalized Medicine", human genetic structure is used for evaluation of the diagnosis, treatment, and prevention of disease. Regarding the limited number of studies regarding this issue in Oral & Maxillofacial diseases, this study was aimed to evaluate the benefits and challenges of this new area (Personalized Medicine) in dental treatments. Materials and Methods: In this study, complete evaluation of abilities and challenges in order to apply the "Personalized Dentistry" in Dental treatments, and also its effect on oral health indexes were done. All the existing related articles were searched with the relevant key words in the scientific data bases of PubMed, Google Scholar, Medline, Scopus, SID and Magiran. Based on the inclusion and exclusion criteria, 5 articles were selected, assessed and summarized. Results: In the evaluated articles, the benefits of "Personalized Dentistry" in dental treatments as targeted and specialized treatment could result in lower time, energy and cost. In addition, its disadvantage as unknown biologic effective factors and also, the cross effects of some of the above items on each other and the treatment procedures were mentioned. Conclusion: Regarding the specialized sciences and diagnostic tools for oral & maxillofacial disease, the benefits of "Personalized Dentistry" application can be increased for special treatments of patients. Also, it could reduce the side effects of conventional therapies and thus, could be introduced as an effective step for better dental treatments.